KEBUGARAN FISIK SISWA YANG MENGIKUTI KEGIATAN EKSTRAKURIKULER OLAHRAGA LEBIH BAIK DIBANDINGKAN DENGAN SISWA YANG HANYA MENGIKUTI MATA PELAJARAN PENJAS DI SMPN 02 MASBAGIK KABUPATEN LOMBOK TIMUR TAHUN PELAJARAN 2016/2017 - -, Makbullah; Muliarta, Made; Pinatih, Gde Ngurah Indraguna; Sri Handari Adiputra, Luh Made Indah; Ngurah, Ida Bagus; Purnawati, Susy (Sport and Fitness Journal; Volume 6, No.2, Mei 2018, 2018)
This research based on practice at junior high school, while physical education lesson we found that the physical fitness of the student are weak. Physical fitness is ability of someone to doing physical activity or make some move in periodic time without have a terrible tired and still have rest of power to dounexpected work.The aims of this research is to knowing the fitness of students who has following the physical education and extracurricular sport more better then the usual student. This research is observational analytic with cross sectional method. Location of this research in 02 masbagik junior high school and using 66 sample divided into 2 groups by random sampling, 33 are usual student, and 33 student that have an extracurricular lesson. Based on analyze of SPSS confirmed that the physical fitness of student that have an extracurricular was better than usual student by 1000 M distance of running test. The usual student got 7,2667±2,12584 minute with median 6,4300 (p = 0,001) while the extra student got 5,4297±1,19317 minute median 5,2300. Based on this research we can confirmed that the level of physical fitness of the student who have the extra lesson was better than the usual student who haven’t the extra lesson.